Effect of Quail Egg Yolk in Tris Based Extender on Cryopreservation of Sahiwal Bull Spermatozoa - Garima Singh,; Saxena, Atul; Neha Chaudhary,; Kumar, Arun; Vikas Sachan,; Anuj Kumar,; Jitendra Kumar Agrawal, (The Indian Journal of Animal Reproduction, 2024)
The present study was designed to determine the effect of different concentrations of quail egg yolk (5%, 10%, 15% and  20%) in tris based semen extender on progressive motility of Sahiwal bull spermatozoa at pre-freeze as well as post-thaw  stage. The progressive motility significantly (P
Keywords: Bull semen; Cryopreservation; Sahiwal; Quail egg yolk